Epidemiology and aetiological diagnosis of corneal ulceration in Madurai, south India. Issue 11 (1st November 1997) - Srinivasan, M; Gonzales, Christine A; George, Celine; Cevallos, Vicky; Mascarenhas, Jeena M; Asokan, B; Wilkins, John; Smolin, Gilbert; Whitcher, John P
Abstract : AIMS/BACKGROUND: To determine the epidemiological characteristics and risk factors predisposing to corneal ulceration in Madurai, south India, and to identify the specific pathogenic organisms responsible for infection. METHODS: All patients with suspected infectious central corneal ulceration presenting to the ocular microbiology and cornea service at Aravind Eye Hospital, Madurai, from 1 January to 31 March 1994 were evaluated. Sociodemographic data and information pertaining to risk factors were recorded, all patients were examined, and corneal cultures and scrapings were performed. RESULTS: In the 3 month period 434 patients with central corneal ulceration were evaluated. A history of previous corneal injury was present in 284 patients (65.4%). Cornea cultures were positive in 297 patients (68.4%). Of those individuals with positive cultures 140 (47.1%) had pure bacterial infections, 139 (46.8%) had pure fungal infections, 15 (5.1%) had mixed bacteria and fungi, and three (1.0%) grew pure cultures of Acanthamoeba . The most common bacterial pathogen isolated was Streptococcus pneumoniae, representing 44.3% of all positive bacterial cultures, followed by Pseudomonas spp (14.4%). The most common fungal pathogen isolated was Fusarium spp, representing 47.1% of all positive fungal cultures, followed by Aspergillus spp (16.1%). CONCLUSIONS: Central corneal ulceration is a common problem in south India and most often occurs after a superficial corneal injury with organic material. Bacterial and fungal infections occur in equal numbers with Streptococcus pneumoniae accounting for the majority of bacterial ulcers and Fusarium spp responsible for most of the fungal infections. These findings have important public health implications for the treatment and prevention of corneal ulceration in the developing world.